Guidelines for Selection and Employment of Consultants by World Bank Borrowers - World Bank (The World Bank, 2004)
The purpose of these Guidelines is to define the Bank's policies and procedures for selecting, contracting, and monitoring consultants required for projects that are financed in whole or in part by loans from the International Bank for Reconstruction and Development (IBRD), credits or grants from the International Development Association (IDA), or grants from the Bank or trust funds administered by the Bank and executed by the beneficiary